1981
DOI: 10.1071/pp9810475
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Organization of Aleurone Cell Wall Components From Wheat and Barley

Abstract: Methylation analysis and hydrolysis with specific enzymes indicates that aleurone cell wall preparations from wheat (Triticum aestivum cv. Insignia) and barley (Hordeum vulgare cv. Clipper) are composed of two main types of polysaccharides, heteroxylans and 1,3;1,4-β-glucans. Small amounts of glucomannan and cellulose are also present. Approximately 1% of a 1,3-β-glucan was also detected in the wall preparations using a specific 1,3-β-glucan exohydrolase. This material probably corresponds to the aniline blue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(127 citation statements)
references
References 50 publications
3
124
0
Order By: Relevance
“…After this time, xyloglucan labeling diminishes in endosperm walls but persists in the surrounding maternal tissues, indicating that xyloglucan is either hydrolyzed from the developing endosperm walls or undergoes modification such that the LM15 antibody does not recognize it (Dwivany et al, 2009). The former possibility seems the more likely given that xyloglucanspecific linkages are not detected in mature endosperm walls by either chemical analysis (Fincher, 1975;Bacic and Stone, 1981b) or by the more sensitive immuno-EM method used in this study (data not shown). Xyloglucan is therefore the second polysaccharide to be shown to undergo turnover in endosperm walls.…”
Section: Xyloglucanmentioning
confidence: 92%
See 1 more Smart Citation
“…After this time, xyloglucan labeling diminishes in endosperm walls but persists in the surrounding maternal tissues, indicating that xyloglucan is either hydrolyzed from the developing endosperm walls or undergoes modification such that the LM15 antibody does not recognize it (Dwivany et al, 2009). The former possibility seems the more likely given that xyloglucanspecific linkages are not detected in mature endosperm walls by either chemical analysis (Fincher, 1975;Bacic and Stone, 1981b) or by the more sensitive immuno-EM method used in this study (data not shown). Xyloglucan is therefore the second polysaccharide to be shown to undergo turnover in endosperm walls.…”
Section: Xyloglucanmentioning
confidence: 92%
“…We were not expecting to detect xyloglucan in the developing endosperm because previous chemical analyses were negative in both the starchy endosperm and aleurone cell walls of mature grain (Fincher, 1975;Bacic and Stone, 1981b) and the amount of xyloglucan in the primary cell walls of the commelinoid monocots is the lowest of any of the flowering plants. However, despite these assumptions, the (1→4)-b-oligoglucoside structures detected by the CBHII-AU probe at 3 and 4 DAP attributed to cellulose binding , were at least partly belonging to the xyloglucan backbone.…”
Section: Xyloglucanmentioning
confidence: 99%
“…These polysaccharides are substituted with ferulic acid and acetic acid 1,2,5 . It is believed that these must be removed by esterases to facilitate the degradation of the polysaccharide by carbohydrases, as in the case in ruminant guts 3,8,[15][16][17][18]26 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Pentosans are major components of these walls, about 71% of aleurone cell walls and 20% of starchy endosperm cell walls 1,2,4,[10][11][12]22 .…”
Section: -2863(9'8-32mentioning
confidence: 99%
“…Hens fed wheat tended to have lower viscosities in the ileum and rectum if their diets were supplemented with xylanase, but in the case of the barley diet the viscosities were actually higher in the ileal contents in hens receiving a-amylase and b-glucanase than in those not receiving enzymes. As NSPs in barley and wheat have different branching structures (Bacic & Stone, 1981), the effectiveness of any particular enzyme will be more related to its appropriateness and efficacy for the substrate than to the total quantity of NSP in the diet. Hence, when evaluating the effectiveness of dietary enzymes, it is necessary to consider these in the context of their use with the specific cereal sources for which they are designed.…”
Section: Discussionmentioning
confidence: 99%